Assessment of Cystatin-C level in Newly Diagnosed Iraqi Children with Nephritic Syndrome - Tahir, Noor; Hashim, Rasha Kareem; Bohan, Alyaa; Mahmood, Luay (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Nephritic syndrome (NS) is a common kidney disease in children that causes protein leakage from the blood into the urine due to glomerular injury. AIM: The aim of this research was to determine the level of Cystatin-C (CysC) and other biochemical parameters in newly diagnosed NS children in Iraq. PATIENTS AND METHODS: Ninety Iraqi children divided into: 50 children with newly diagnosed NS (28 boys and 22 girls) aged between (4 and 16) years, and 40 healthy control children (20 boys and 20 girls) aged between (5 and 16) years, who were attending Al-Yarmouk Teaching Hospital, Baghdad. RESULTS: There was a significant increase in blood urea, serum total cholesterol (S.TC), and serum low density lipoprotein (S.LDL) and a significant decreased of serum creatinine (S. creatinine), protein/creatinine ratio, serum total bilirubin, serum albumin, and serum high density lipoprotein, while a highly significant increased (p < 0.001) of CysC levels in children with newly diagnosed NS when compared with control group. A significant positive correlation between CysC level versus systolic blood pressure, body mass index, diastolic blood pressure, S.TC, S. LDL cholesterol (S.LDL-C), S. Total Bilirubin, S. Albumin, S. Total protein, and B. urea, while a significant negative correlation was found between CysC level versus serum low density lipoprotein cholesterol and estimated glomerular filtration rate in children with newly diagnosed NS. CONCLUSION: It may come to the conclusion that CysC can be the best predictor of overall efficacy than creatinine and in the diagnosis of any damage to the kidney in children with NS.